PELATIHAN PENULISAN KARYA ILMIAH PARA GURU SMAN SE-KABUPATEN JOMBANG DI ERA DIGITAL - Raharjo, Resdianto Permata; Supratno, Haris; Indriyanti, Aries Dwi; Amalia Shofiani, Arisni Kholifatu (ABIDUMASY, 2024)
In the digital era, a teacher or lecturer will not find it difficult to find literature through the internet or the digital world. A teacher or lecturer who does not read many books or literature, they lack ideas or ideas that are poured into writing scientific papers so that they consider writing scientific papers difficult. The purpose of the Community Service activity is to provide knowledge and skills for teachers of SMAN in Jombang Regency which includes: (1) techniques for writing scientific papers published in Sinta National Journals 1-5 and (2) techniques for writing scientific papers published in International Journals. Changes in government policy make teachers no longer able to interest in making journal articles, from this activity intern retrain the enthusiasm of teachers in writing scientific articles with the help of technology in the modern era. The target of community service is MGMP Indonesian language teachers in the Jombang area. The priority program that has been agreed by the PKM Team with MGMP is to increase the knowledge and skills of writing scientific papers of Indonesian language teachers in Jombang Regency so that their articles can be published in national and international journals. The methods used in the PKM are discussions and assignments. The PKM results published the work of teachers who had been given training in the SINTA 5 journal, namely the DISASTRI UNHASY journal.